Stanisław Orzechowski as a political writer, with particular emphasis on his Speech to the Polish Nobility - Wicher, Andrzej (Jakub Przyłuski (1512–1554): Outline of life and literary work against the background of the epoch, 2022)
This paper is primarily a presentation of the remarkable figure of Stanisław Orzechowski (1513–1566), an outstanding Polish writer and political and religious polemicist. His attitude may raise doubts, considering that he was first associated with the Protestant Reformation, but then he became a champion of the Catholic Counter-Reformation, but in his writings he shows himself to be a foremost expert on the Polish political scene and systemic issues. His Speech to the Polish Nobility (1560), which was an introduction to the work of Jakub Przyłuski, entitled The Laws, Statutes and Privileges of the Kingdom of Poland, praises, on the one hand, the Polish political system and the political mind of the nobility, but on the other hand, it contains some premonitions about the future threats that were soon to materialize. The author of the paper emphasizes the organic relationship of this work with the study by Przyłuski and tries to bring out such threads of Orzechowski’s thought that were continued also in our contemporary times.